PENYULUHAN KESEHATAN SADARI DI POLI OBGYN RUMAH SAKIT PANTI WALUYA SAWAHAN MALANG - Pertiwi Perwiraningtyas; Sirli Mardianna Trishinta; Susmini (Jurnal LENTERA, 2021)
The prevalence of breast cancer in women of childbearing age is increasing. This is reinforced by women's ignorance of Breast Self-Examination. The purpose of this activity is to increase women's knowledge about breast cancer and breast self-examination in order to reduce the prevalence of breast cancer. This activity was carried out for one day at Panti Waluya Sawahan Hospital, Malang with 20 respondents, with the method of providing health education which was previously given a pre-test to measure the knowledge of the respondents. After being given education by means of leaflets, demonstrations and discussions, then the respondents were re-measured their knowledge with a post test. The results obtained from this activity are, before the counseling, it was found that most of the respondents had sufficient knowledge, while after that, it was found that all respondents had good knowledge. This health education activity is included in health promotion efforts to form motivation and skills which are further useful in increasing self-efficacy in early detection of breast cancer. It is proven that counseling about breast self-examination can increase knowledge and insight of all women of childbearing age with knowledge levels in the good category.